2017
DOI: 10.14260/jemds/2017/958
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice (Kap) of Rubella Vaccination in Adolescent Girls Attending Gynaecology Opd at BRD Medical College, Gorakhpur

Abstract: BACKGROUNDRubella, also called German measles, is a disease of childhood. In the absence of pregnancy, it is usually clinically manifested as a mild self-limited infection. But a woman infected with the Rubella virus during the early stage of pregnancy has a 90% chance of transmitting it to the foetus. The virus can cause hearing impairments, eye and heart defects and brain damage in newborns, and even spontaneous abortion and foetal deaths. Of the 1,10,000 children born with CRS every year globally, an estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
2
0
0
Order By: Relevance
“…This might explained by the women had children and give them immunization of MMR. This agreed with Kumari et al [19] who found that 13.02% of participants stated that rubella can be prevented by vaccine.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This might explained by the women had children and give them immunization of MMR. This agreed with Kumari et al [19] who found that 13.02% of participants stated that rubella can be prevented by vaccine.…”
Section: Discussionsupporting
confidence: 91%
“…This due to that most of pregnant women didn't hear on this disease before. This agreed with Kumari et al [19] who observed that 86.98% of recipients didn't know the adverse effect of rubella on pregnancy and fetus.…”
Section: Discussionsupporting
confidence: 90%